Speech Act Analysis on Facebook Chats - Riski Safitri; Efendi Efendi; Titik Hardewi Yani; Yanti Nazmai Ekaputri; Veni Veni; Dino Adi Putra; Andri Yanto (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
This study focuses on speech act on facebook chat. The purposes of this study are to identify the types of speech act and describe the functions of each type of the speech act on facebook chat. This study employed descriptive qualitative research in which the researcher uses observation and documentation and methods to collect data. The data of this research is written utterances on Facebook chats. The results of this study show that from 90 data the researcher finds five types of speech act. There are 20 data or 22% from representatives, 18 data or 20% from directives, 15 data or 17% from commissives, 26 data or 29% from expressive, and 11 data or 12% from declarations. Each type of speech act on Facebook chat has its function. Representatives act have functions describing, asserting, and informing; directives act has functions commanding, requesting, inviting, forbidding, suggesting; commissives act have functions promising, threatening, offering; expressives act have functions thanking, apologizing, welcoming, and congratulating; and declarations act have function declaring.